STUDY OF RISK FACTORS AND PROGNOSIS OF MYOCARDIAL INFARCTION IN THE POPULATION OF MEN OF DIFFERENT AGES ACCORDING TO THE RESULTS OF SCREENING IN THE ANDIJAN REGION - Yo‘liboyev S.I.; Vakhabov B. M.; Bektasheva G.M. (Western European Studies, 2024)
According to modern data, the decrease in mortality from MI in recent years in men, especially of working age, occurs to a lesser extent than in women of the same age group. The persistence of high morbidity and mortality in Russia from CVD, including among the male population, is largely due to insufficient influence on the main risk factors for coronary heart disease and MI, which are: smoking, unhealthy diet, low physical activity and psychosomatic risk factors, arterial hypertension (AH), disorders of carbohydrate metabolism, including diabetes mellitus (DM), as well as lipid metabolism disorders and obesity.
Keywords: cardiology; ischemic heart disease; myocardial infarction